2022
DOI: 10.1371/journal.pcbi.1010394
|View full text |Cite
|
Sign up to set email alerts
|

TreeKnit: Inferring ancestral reassortment graphs of influenza viruses

Abstract: When two influenza viruses co-infect the same cell, they can exchange genome segments in a process known as reassortment. Reassortment is an important source of genetic diversity and is known to have been involved in the emergence of most pandemic influenza strains. However, because of the difficulty in identifying reassortments events from viral sequence data, little is known about its role in the evolution of the seasonal influenza viruses. Here we introduce TreeKnit, a method that infers ancestral reassortm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 31 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…We demonstrated that finding the maximum parsimony number of remove-and-rejoin moves between sampled segment trees is not a consistent way to count the correct number of visible reassortment events, unless the first-infection tree is known. Existing topology-based methods (like those implemented in TreeKnit [22]) could be adapted to search the space of remove-and-rejoin moves for a set of segment trees given a first-infection tree. It is unlikely that the first-infection tree would be known, so a more reasonable way to deal with conditioning on the first-infection tree is to treat it as a nuisance variable that we would need to integrate out in the context of some prior distribution over the space of first-infection trees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that finding the maximum parsimony number of remove-and-rejoin moves between sampled segment trees is not a consistent way to count the correct number of visible reassortment events, unless the first-infection tree is known. Existing topology-based methods (like those implemented in TreeKnit [22]) could be adapted to search the space of remove-and-rejoin moves for a set of segment trees given a first-infection tree. It is unlikely that the first-infection tree would be known, so a more reasonable way to deal with conditioning on the first-infection tree is to treat it as a nuisance variable that we would need to integrate out in the context of some prior distribution over the space of first-infection trees.…”
Section: Discussionmentioning
confidence: 99%
“…We first simulated the full population history such that the expected population size is ( I = 100), with rates λ = 5, µ = 4.75, Ψ = 0.25, ρ = ρ A + ρ B + ρ AB = 0.2, until 50 samples were obtained. These parameters are chosen to align with simulations in previous literature [22, 27], meanwhile making sure the frequencies of aforementioned situations are significant enough. For each of the number of visible reassortments, ranging from 5 to 14, we produced 100 replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we focused our reassortment analysis on HA and NA sequences, sampling 1,607 viruses collected between January 2016 and January 2018 with sequences for both genes. We inferred HA and NA phylogenies from these sequences and applied TreeKnit to both trees to identify maximally compatible clades (MCCs) that represent reassortment events [11]. Of the 208 reassortment events identified by TreeKnit, 15 (7%) contained at least 10 samples representing 1,049 samples (65%).…”
Section: Joint Embeddings Of Hemagglutinin and Neuraminidase Genomes ...mentioning
confidence: 99%
“…When the sets are maximally different, VI is log N where N is the total number of samples. To make VI values comparable across datasets, we normalized each value by dividing by log N , following the pattern used to validate TreeKnit's MCCs [11]. Unlike other standard metrics like accuracy, sensitivity, or specificity, VI distances do not favor methods that tend to produce more, smaller clusters.…”
Section: Clustering Of Samples In Embeddingsmentioning
confidence: 99%